2022
DOI: 10.3389/fpls.2022.970865
|View full text |Cite
|
Sign up to set email alerts
|

A QTL approach in faba bean highlights the conservation of genetic control of frost tolerance among legume species

Abstract: Frost is a major abiotic stress of winter type faba beans (Vica faba L.) and has adverse effects on crop yield. Climate change, far from reducing the incidence of frost events, is making these phenomena more and more common, severe, and prolonged. Despite the important interaction that the environment has in the tolerance of faba bean to frost, this trait seems to have good levels of heritability. Several QTLs for frost tolerance have already been reported, however, a more robust identification is needed to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…Carrillo-perdomo et al (2020) constructed a highdensity genetic map containing gene-based SNP markers with a length of 1,547.71 cM, and an average distance of 0.89 cM. Recently, an integrated genetic linkage map containing 6,895 SNPs, with a length of 3,324.48 cM was constructed from two F 2 populations by Li et al (2023).The construction of a fine linkage map for faba bean can greatly improve the efficiency of related genetic research and crop breeding and enable the establishment of marker selection and QTL mapping associated with economically important traits (Khazaei et al, 2014;Aguilar−Benitez et al, 2021;Gutierrez and Torres, 2021;Carrillo-Perdomo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Carrillo-perdomo et al (2020) constructed a highdensity genetic map containing gene-based SNP markers with a length of 1,547.71 cM, and an average distance of 0.89 cM. Recently, an integrated genetic linkage map containing 6,895 SNPs, with a length of 3,324.48 cM was constructed from two F 2 populations by Li et al (2023).The construction of a fine linkage map for faba bean can greatly improve the efficiency of related genetic research and crop breeding and enable the establishment of marker selection and QTL mapping associated with economically important traits (Khazaei et al, 2014;Aguilar−Benitez et al, 2021;Gutierrez and Torres, 2021;Carrillo-Perdomo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental knowledge and molecular tools for breeding have been boosted on the legume tolerance against abiotic stresses after peas entered the genomic era with the pea Caméor genome sequenced. Diverse studies have been performed to better understand the legume tolerance mainly to drought [64][65][66][67][68] and heat [19,68,70] stresses but also to frost [73,74], cold [75], and salinity [78]. For drought, the pea cv.…”
Section: Ascochyta Blight Resistancementioning
confidence: 99%
“…Syntenic studies were also performed between QTLs identified in faba bean for frost tolerance and the pea cv. Caméor genome and conservation of genetics for this trait were observed [74]. Mapping of transcriptome and miRNA sequencing reads against pea cv.…”
Section: Ascochyta Blight Resistancementioning
confidence: 99%